EXPLORING THE IMPACT OF GENDER EQUALITY ON LANGUAGE LEARNING OUTCOMES: A COMPARATIVE ANALYSIS OF EDUCATIONAL PRACTICES AND STUDENT EXPERIENCES - Sobirova Elgiza Alibek kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
The connections between language acquisition and gender equality has been a crucial topic of inquiry in educational studies in recent years. The impact of gender dynamics on language learning and its consequences for instructional strategies in various educational situations are examined in this study. The study draws attention to enduring differences in language learning outcomes across genders by examining historical and modern viewpoints on gender in education. It examines the theoretical frameworks that support these processes, such as feminist pedagogy and social constructivism, and it surveys the body of research that shows the nuanced connection between language competency and gender norms. This study uses a mixed-methods approach in terms of methodology, combining qualitative information from interviews and classroom observations with quantitative data from language competency tests. Students from a variety of backgrounds participate, enabling a comprehensive knowledge of the experiences of various genders in language learning settings. The results show that boys usually show more confidence, although girls tend to show stronger language ability and involvement, indicating that socialization and cultural expectations greatly influence their experiences.